2020
DOI: 10.1038/s41388-020-01498-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oncogene PTPN13 inactivation by hepatitis B virus X protein counteracts IGF2BP1 to promote hepatocellular carcinoma progression

Abstract: Hepatitis B x protein (HBx) affects cellular protein expression and participates in the tumorigenesis and progression of hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC). Metabolic reprogramming contributed to the HCC development, but its role in HBV-related HCC remains largely unclear. Tyrosine-protein phosphatase nonreceptor type 13 (PTPN13) is a significant regulator in tumor development, however, its specific role in hepatocarcinogenesis remains to be explored. Here, we found that decreased P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…ARRB1 has been indicated to promote HCC, and was upregulated by hepatitis B virus X protein (HBx) in mouse models [ 59 ]. Interestingly, among other candidate genes, some genes are related to the progression of HCC, including, GATAD1 [ 44 , 45 ], FOXK1 [ 46 ], RALGAPA2 [ 47 ], PDE4A [ 48 ], TRIP6 [ 49 ], SPTBN1 [ 53 ], PTP4A3 [ 54 ], TRIM4 [ 56 ], and LMNB1 [ 60 ]. These results suggest that the 36 candidate genes are associated with the functions of HBV and hepatocytes; however, this association needs to be further validated.…”
Section: Discussionmentioning
confidence: 99%
“…ARRB1 has been indicated to promote HCC, and was upregulated by hepatitis B virus X protein (HBx) in mouse models [ 59 ]. Interestingly, among other candidate genes, some genes are related to the progression of HCC, including, GATAD1 [ 44 , 45 ], FOXK1 [ 46 ], RALGAPA2 [ 47 ], PDE4A [ 48 ], TRIP6 [ 49 ], SPTBN1 [ 53 ], PTP4A3 [ 54 ], TRIM4 [ 56 ], and LMNB1 [ 60 ]. These results suggest that the 36 candidate genes are associated with the functions of HBV and hepatocytes; however, this association needs to be further validated.…”
Section: Discussionmentioning
confidence: 99%
“…Its methylation is consistently associated with decreased PTPN13 expression [103], and has been observed in many hematologic (94% of 16 non-Hodgkin lymphoma cell lines, 50% of 6 Hodgkin lymphoma cell lines) and solid cancer cell lines (67% of 12 HCC cell lines, 60% of 10 gastric cancer cell lines, and 30% of 10 breast cancer cell lines). Similarly, Yeh et al reported that the PTPN13 promoter is methylated in 66% of 12 HCC samples without loss of heterozygosity (LOH) of chromosome 4q [104]. Moreover, Wang et al found that the PTPN13 promoter is methylated in 60% of 47 diffuse large B cell lymphoma samples, compared with 6.3% of 16 non-tumor tissue samples [112].…”
Section: Transcriptional Regulation Mediated By Transcription Factorsmentioning
confidence: 98%
“…More recently, Yan Y. et al demonstrated that, in HCC, the hepatitis B virus X protein regulates PTPN13 expression via the DNA methyltransferase 3A, which binds to the PTPN13 promoter and induces the hypermethylation of its CpG islands. This loss of PTPN13 leads to an increase in c-Myc levels and signaling through the loss of its competitive interaction with IGFP2B1 that protects c-Myc mRNA from degradation [104].…”
Section: Transcriptional Regulation Mediated By Transcription Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silencing miR-132 inhibited the aberrant formation of dendritic spines and chronic spontaneous seizures in a lithiumpilocarpine-induced epileptic mouse model (Yuan et al, 2016). Experiments with cultured epileptic neurons suggesting that miR-132 silencing exerted a neuroprotective effect through the miR-132/p250GAP/Cdc42 pathway (Yuan et al, 2016). miR-204 directly targets and downregulates TrkB protein in various diseases (Xiang et al, 2016).…”
Section: Mirna-based Therapeutic Approaches For Epilepsymentioning
confidence: 99%